Access to Drinking Water, Sanitation, and Hand Hygiene Facilities in the Peri-Urban and Informal Settlements of Hosanna Town, Southern Ethiopia - Abiot Abera Aydamo; Sirak Robele Gari; Seid Tiku Mereta (SAGE Publishing, 2023)
Access to water, sanitation, and hygiene (WASH) facilities and practices have been extensively studied in urban and rural areas. However, there is a paucity of information on the coverage of water, sanitation, and hygiene facilities in the peri-urban and informal settlement areas, which could potentially exacerbate the spread of water, sanitation, and hygiene-related diseases. Therefore, this study was designed to examine access to drinking water, sanitation, and hand hygiene facilities and their determinant factors in the peri-urban and informal settlements of Hosanna town. A community-based cross-sectional study involving 292 households was conducted in 3 kebeles of Hosanna town. The primary data was collected using a pretested structured questionnaire and an observational checklist. Bivariate and multivariable logistic regressions were used to analyze the data. All the households (100%) had access to piped water on and off-premises, but the reliability of the water sources was a big challenge. Findings revealed that only 35.1% and 16.8% of the households had basic sanitation and basic handwashing facilities, respectively. Households with a middle income were identified as a determinant factor for the presence of piped water on premises (AOR = 2.23; 95% CI = 1.24-4.00), improved sanitation (AOR = 2.17; 95% CI = 1.17-4.03) and handwashing facilities (AOR = 4.36; 95% CI = 1.98-9.62). Piped water on premises was also another strong predictor of the availability of improved sanitation (AOR = 3.34; 95% CI = 1.99-5.62) and handwashing facilities (AOR = 8.18; 95% CI = 4.08-16.42). The majority of the studied households living in the selected peri-urban and informal settlements had access to unreliable drinking water sources. The study also revealed that households had poor access to basic sanitation and basic handwashing facilities. Hence, the findings call for solid government interventions to improve the reliability of the drinking water sources, basic sanitation coverage, and availability of basic handwashing facilities.